The pattern of underlying cause of death in patients with inflammatory bowel disease in England: a record linkage study - Chu, Thomas P.C.; Moran, Gordon W.; Card, Timothy R. (Oxford University Press, 2016)
Background and Aims: Numerous studies have established that mortality risk in IBD patients is higher than the general population, but the causes of death have seldom been examined. We aimed to describe causes of death in IBD.